UV-B induces the expression of flavonoid biosynthetic pathways in blueberry (Vaccinium corymbosum) calli - Song, Yan; Ma, Bin; Guo, Qingxun; Zhou, Lianxia; Lv, Changyi; Liu, Xiaoming; Wang, Jianlei; Zhou, Xintong; Zhang, Chunyu (Frontiers in Plant Science, 2022)
Ultraviolet-B (UV-B) radiation is an environmental signal that affects the accumulation of secondary metabolites in plants. In particular, UV-B promotes flavonoid biosynthesis, leading to improved fruit quality. To explore the underlying molecular mechanism, we exposed blueberry (Vaccinium corymbosum) calli to UV-B radiation and performed a transcriptome deep sequencing (RNA-seq) analysis to identify differentially expressed genes (DEGs). We detected 16,899 DEGs among different treatments, with the largest number seen after 24 h of UV-B exposure relative to controls. Functional annotation and enrichment analysis showed a significant enrichment for DEGs in pathways related to plant hormone signal transduction and phenylpropanoid and flavonoid biosynthesis. In agreement with the transcriptome data, flavonol, anthocyanin and proanthocyanidin accumulated upon UV-B radiation, and most DEGs mapping to the phenylpropanoid and flavonoid biosynthetic pathways using the KEGG mapper tool were upregulated under UV-B radiation. We also performed a weighted gene co-expression network analysis (WGCNA) to explore the relationship among genes involved in plant hormone signal transduction, encoding transcription factors or participating in flavonoid biosynthesis. The transcription factors VcMYBPA1, MYBPA2.1, MYB114, MYBA2, MYBF, and MYB102 are likely activators, whereas MYB20, VcMYB14, MYB44, and VcMYB4a are inhibitors of the flavonoid biosynthetic pathway, as evidenced by the direction of correlation between the expression of these MYBs and flavonoid biosynthesis-related genes. The transcription factors bHLH74 and bHLH25 might interact with MYB repressors or directly inhibited the expression of flavonoid biosynthetic genes to control flavonoid accumulation. We also observed the downregulation of several genes belonging to the auxin, gibberellin and brassinosteroid biosynthetic pathways, suggesting that MYB inhibitors or activators are directly or indirectly regulated to promote flavonoid biosynthesis under UV-B radiation.